Prosthetic oral rehabilitation in a child patient with ectodermal dysplasia: Case report (Research, Society and Development, 2024)
Ectodermal dysplasia (ED) represents a rare genetic condition characterized by defects in the development of structures originating from the ectoderm. This can result in abnormalities such as the absence or underdevelopment of tissues such as skin, hair, nails, teeth and certain glands, including sebaceous and sweat glands. Often, teeth are sparse and have abnormal shapes in their crowns, and in rarer cases, a complete absence of teeth may occur. The diagnosis of this condition generally occurs in childhood, and dental management may involve the use of dental prostheses, whether partial or complete, and fixed or removable, adapted according to the patient's specific situation. This study aims to discuss the case of a four-year-old boy who was seen at the dental clinic at Universidade Tiradentes, presenting with anhidrotic ED. The application of a removable partial denture for both dental arches was recommended, accompanied by psychological support. The importance of early diagnosis is highlighted to prevent negative impacts on dental aesthetics and occlusion, which can significantly compromise the child's well-being. It is crucial that the dental professional has adequate knowledge about the variants of ED to ensure effective intervention and improve the patient's dental conditions.